An updated review of clinical methods in the assessment of ageing skin – New perspectives and evaluation for claims support. (24th August 2018) - Bielfeldt, S.; Springmann, G.; Seise, M.; Wilhelm, K.‐P.; Callaghan, T.
Abstract: With the advancement of skin research, today's consumer has increased access to an informed understanding of ageing skin and its appendages, together with a plethora of targeted products to meet such needs. In recent years, increased legislative demands for quality evidential claims support have led not only to the development and validation of clinical methods to measure and quantify ageing skin, but also a clearer understanding of the skin ageing process–especially the impact of both its internal and external environments–as well as a tougher stance on clearly unjustifiable claims. Traditional testing methods used to research and evaluate anti‐ageing products claim to employ sophisticated instruments. Today, however, since the term anti‐ageing can be considered a misnomer, intelligent use of combined more advanced clinical methods has enabled the development of technologically improved consumer products providing enhanced efficacy and targeted performance. Non‐invasive methods for the assessment and quantification of the causes of ageing skin provide tools to the clinical researcher as defined by key clinically observed ageing parameters. Where evidence requires additional support, a number of clinical procedures evaluating ageing skin and hair products are combined with invasive procedures, thus enabling an added value to product claims. As discussed herein, given the enhanced understanding of ageing, we provide an update to our previous reviews of clinical methods used in the assessment of skin ageing, to include the wider aspects of environmental exposure; skin pigmentation; microbiome disturbance; surface topography; colour, radiance, and pH; and structural integrity–all requiring a disciplined approach to their use in dermatological investigations and product claims evidence.